THE CONCEPTUALISATION OF PERSONABLE VILLAINY AND WINSOME KNAVES: ENTER ANAKIN SKYWALKER AND CORIOLANUS SNOW - Emir Z. Muhić (Filolog, 2023)
The multifaceted human personality apparatus tirelessly and somewhat incessantly keeps on giving rise to both surprising and equally dishearteningly bland revelations as regards to how the idiosyncratic denizens of this blue-hued marble encode and decipher various cultural phenomena. This is particularly pertinent in view of the relentless endeavours to peel off the deeper layers of the pseudo-proverbial human cognitive onion. It would doubtless come across as supremely hauteur-suffused should a paper harbour a latent claim to fame in terms of comprehensiveness and immaculate insight into what appears to be nothing short of a rabbit hole-like bottomless pit of hopeless scholarly efforts at inching ever so slightly more towards the neighbourhood of the metanarrative fount of all creativity and meaning. Therefore, the succeeding pages shall do away with that specific delusion and attempt to labour under merely one and relatively monotonous question: how do we go about explaining the impulse to root for the prototypical villain instead of bowing to the infinitely promulgated notion of archetypal goodness?